Evaluation of service quality of academic libraries : a case study of NTU libraries 1 and 2. - Tay, Joycelyn Kee Wah. (2008)
A key measure of service quality is based on the disconfirmation theory, which measures the difference between perceived service level and expected service level. SERVQUAL, a measurement tool was developed and adapted for use in libraries. This study applied the SERVQUAL tool to identify service gaps in the NTU libraries.